Pervasive Computing Paradigms for Mental Health 4th International Symposium, MindCare 2014, Tokyo, Japan, May 8-9, 2014, Revised Selected Papers - Cipresso, Pietro; Matic, Aleksandar; Lopez, Guillaume (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering, 2014)
This book constitutes the reviewed post-proceedings of the 4th International ICST Conference on Pervasive Computing Paradigms for Mental Health, MindCare 2014, held in Tokyo, Japan, in May 2014. The 16 revised full papers presented were carefully reviewed and selected from 26 submissions for inclusion in the proceedings. The papers are organized in topical sections on recognition and assessment, mental health management, improving communication, depression, and self-applied treatments.